The impact of point-of-care HbA1c testing and intensified clinical care on glycaemic control in patients with type 2 diabetes at Khayelitsha Community Health Centre - Allerton, Joshua (Stellenbosch : Stellenbosch University, 2019)
Thesis (MMed)--Stellenbosch University, 2019.